The Effectiveness of Olive Oil Application in Reducing Pruritus and Improving Comfort Among Hemodialysis Patients at Putri Hijau Hospital, Medan - Eka Nugraha V. Naibaho; Mhd Alfi Syahrin Nursanjaya; Edisyah Putra Ritonga; Nataria Yanti Silaban; Yuni Shanti Ritonga; Syahrul Handoko Nainggolan (CV. Devitara, 2025)
Hemodialysis is a therapeutic intervention used to replace kidney function when the kidneys are no longer able to perform their physiological roles adequately, and it is initiated when conservative treatment fails to maintain renal function. Uremic pruritus is a commonly used term referring to a dermatological symptom characterized by an itching sensation that provokes the urge to scratch and is highly prevalent among patients undergoing hemodialysis. The administration of olive oil was conducted to evaluate its long-term effect on reducing the severity of pruritus. The objective of this study was to determine the effectiveness of olive oil application in reducing pruritus among hemodialysis patients at Putri Hijau Hospital, Medan. This study employed a pre-experimental design with a one-group pretest–posttest approach. The research was conducted from February to April 2025 at Putri Hijau Hospital, Medan. The total population consisted of 60 patients, and a sample of 37 respondents was selected using purposive sampling. Bivariate analysis was performed using the Wilcoxon signed-rank test. The results showed that on the first day prior to olive oil application, the majority of hemodialysis patients experienced unbearable itching, with 18 respondents (48.6%). On the fifth day after the intervention, the majority of patients reported mild itching, with 19 respondents (51.4%). Based on the Wilcoxon test results, the significance value was less than 0.05, indicating a statistically significant effect. The study findings demonstrate that olive oil application significantly reduced pruritus among hemodialysis patients at Putri Hijau Hospital, Medan, with a two-tailed significance value of 0.000 (<0.05).